Rietz och riksspråket - Thelin, Eva (Nordiske Studier i Leksikografi, 2018)
The most recent dialect dictionary covering all Swedish dialects appeared in 1862–67, published by Johan Ernst Rietz. In those days, dialect dic-tionaries only consisted of words which did not appear in standard Swe-dish. Rietz, though, does include some standard words and in the fore-word to the dictionary he specifies his criteria for entering them. In this article I examine what standard words Rietz has actually included (based on the words beginning with h-) and how well they correspond to his cri-teria.